Sulfur fertilization technology in the Argentine Pampas region : a review - Torres Duggan, Martín (2012)
Sulfur (S) deficiencies in grain crops have become increasingly frequent worldwide, including the Argentine Pampas region, located in South America. The objective of this work is to review recent research literature regarding S fertilization in the Argentine Pampas region, with emphasis on technological issues. The S fertilization in this region has grown sharply over recent years and, simultaneously, more scientific literature has been generated. A knowledge gap is recognized on field research studies related to elemental sulfur (ES) fertilization and its relative agronomic effectiveness in comparison to soluble S sources. By far, solid sulfate fertilizers are the most widespread S sources applied by farmers in the Pampas region. Nonetheless, application of liquid sources has increased over recent times. Overall, similar agronomic performance among sulfate sources has been reported. Additionally, similar effectiveness was documented between micronized ES and sulfate sources for different crops, with the exception of some site-specific conditions where effectiveness of sulfate sources may outperform ES. This review manuscript contributes to synthesize current knowledge regarding S fertilization technology and identify research needs in this matter.